High Phobic Anxiety Is Related to Lower Leukocyte Telomere Length in Women - Okereke, Olivia I. (Public Library of Science, 2012)
BACKGROUND: Chronic psychological distress has been linked to shorter telomeres, an indication of accelerated aging. Yet, little is known about relations of anxiety to telomeres. We examined whether a typically chronic form of anxiety – phobic anxiety – is related to telomere length. METHODOLOGY/PRINCIPAL FINDINGS: Relative telomere lengths (RTLs) in peripheral blood leukocytes were measured by quantitative real-time polymerase chain reaction among 5,243 women (aged 42–69 years) who: were participants in the Nurses' Health Study; were controls in prior case-control studies of telomeres and disease, or randomly selected healthy participants in a cognitive function sub-study; had completed the Crown-Crisp phobic index proximal to blood collection. Adjusted least-squares mean RTLs (z-scores) were calculated across phobic categories. Higher phobic anxiety was generally associated with lower RTLs (age-adjusted p-trend = 0.09); this association was similar after adjustment for confounders – paternal age-at-birth, smoking, body mass index (BMI) and physical activity (p-trend = 0.15). Notably, a threshold was identified. Among women with Crown-Crisp<6 points, the multivariable-adjusted least-squares mean RTL z-score = 0.02 standard units; however, among the most phobic women (Crown-Crisp≥6), the multivariable-adjusted least-squares mean RTL z-score = −0.09 standard units (mean difference = −0.10 standard units; p = 0.02). The magnitude of this difference was comparable to that for women 6 years apart in age. Finally, effect modification by BMI, smoking and paternal age was observed: associations were stronger among highly phobic women with BMI≥25 kg/m(2), without smoking history, or born to fathers aged ≥40 years. CONCLUSIONS/SIGNIFICANCE: In this large, cross-sectional study high phobic anxiety was associated with shorter telomeres. These results point toward prospective investigations relating anxiety to telomere length change.